Reciprocally Interlocking Boards of Directors and Executive Compensation - Hallock, Kevin F. (Journal of Financial and Quantitative Analysis, 1997)
Is executive compensation influenced by the composition of the board of directors?About 8% of chief executive officers (CEOs) are reciprocally interlocked with another CEO-the current CEO of firm A serves as a director of firm B and the current CEO of firm B serves as a director of firm A. Roughly 20% of firms have at least one current or retired employee sitting on the board of another firm and vice versa.I investigate how these and other features of board composition affect CEO pay by using a sample of 9,804 director positions in America's largest companies.CEOs who lead interlocked firms earn significantly higher compensation.Also, interlocked CEOs tend to head larger firms.After controlling for firm and CEO characteristics, the pay gap is reduced dramatically.However, when firms that are interlocked due to documented business relationships are considered not interlocked, the measured return to interlock is as high as 17%.There also is evidence that the return to interlock was higher in the 1970s than in the early 1990s.